Low hemoglobin, albumin, lymphocyte, and platelet score increases symptomatic intracranial hemorrhage risk in thrombectomy patients - Shuaiyu Chen; Zhihang Huang; Jingwen Qi; Bin Wei; Yan E; Chunmei Liu; Yingdong Zhang; Xiaohao Zhang (Frontiers in Neurology, 2025)
BackgroundThe HALP index, a composite biomarker integrating hemoglobin, albumin, lymphocyte, and platelet parameters, reflects both immunological competence and nutritional status. We therefore conducted this retrospective analysis to assess the correlation between HALP score and the risk symptomatic intracranial hemorrhage (sICH) risk in patients receiving mechanical thrombectomy (MT).MethodsThis retrospective study included patients with acute ischemic stroke due to anterior circulation large vessel occlusion who underwent MT between October 2019 and July 2024. The HALP index was calculated based on admission laboratory parameters. The sICH was diagnosed according to Heidelberg Bleeding Classification criteria within 72 h post-procedure. Multivariate logistic regression analysis was performed to identify independent association between pretreatment HALP score and sICH risk after adjusting for covariates.ResultsA total of 735 patients (mean age, 71.3 ± 10.9 years; 423 male) were enrolled in this study. sICH was diagnosed in 82 patients (11.2%) during hospitalization. After adjusting for demographic characteristics and other covariates, multivariate logistic regression analysis revealed that a low HALP index was significantly associated with an elevated risk of sICH (odds ratio: 1.058, 95% confidence interval: 1.024–1.094, p = 0.001). findings were obtained when the HALP score was analyzed as a categorical variable. Additionally, the restricted cubic spline analysis confirmed a linear inverse relationship between the HALP index and the risk of sICH following MT (p = 0.551 for non-linearity).ConclusionOur data confirmed a significant inverse correlation between the HALP score and the sICH risk in patients treated with MT. This suggests that the HALP score may serve as a valuable tool for monitoring and managing sICH risk in ischemic stroke patients following reperfusion therapy.